Histological study of donor/recipient feasibility in distal nerve transfer for the upper limb nerve injury - Akira Kodama; Atsushi Kunisaki; Teruyasu Tanaka; Shigeki Ishibashi; Kentarou Tsuji; Masaru Munemori; Goki Kamei; Koji Ikegami; Nobuo Adachi (PLoS ONE, 2025)
This study aimed to histologically investigate whether the compatibility of donor and recipient nerves in distal nerve transfer for radial and ulnar nerve palsy is suitable for restoring nerve function. Partial median to radial nerve transfer for radial nerve palsy and partial median to ulnar nerve transfer for ulnar nerve palsy were performed in 10 cadaveric upper limbs fixed using the Thiel technique. Histological analysis of the nerve samples at the coaptation site focused on the number of myelinated axons. Each recipient and donor nerve was identified in all specimens without any anatomical variations. While median-radial nerve transfer techniques showed an adequate number of donor axons, median-ulnar nerve transfer techniques showed a shortage of donor axons. The insufficiency of donor axons compared to the recipient axons may explain the challenges in reinnervating the recipient muscles. Combining the two different nerve transfers may compensate for the shortage of donor axons and improve motor recovery. Type of study and Level of evidence: Therapeutic, Level III.